A multicenter study on PIVKA reference interval of healthy population and establishment of PIVKA cutoff value for hepatocellular carcinoma diagnosis in China. (20th March 2017) - Qin, X.; Tang, G.; Gao, R.; Guo, Z.; Liu, Z.; Yu, S.; Chen, M.; Tao, Z.; Li, S.; Liu, M.; Wang, L.; Hou, L.; et al.
Summary: Introduction: The aim of this study was to investigate the reference interval of protein‐induced vitamin K absence or antagonist‐II (PIVKA‐II) in China population and to evaluate its medical decision level for hepatocellular carcinoma (HCC) diagnosis. Methods: To determine the reference range for Chinese individuals, a total of 855 healthy subjects in five typical regions of China were enrolled in this study to obtain a 95% reference interval. In a case–control study which recruited the subjects diagnosed with HCC, metastatic liver cancer, bile duct cancer, hepatitis, cirrhosis, other benign liver diseases and the subjects administrated anticoagulant, receiver operating characteristic analysis was used to determine PIVKA‐II cutoff value for a medical decision. Results: The concentration of PIVKA‐II had no relationship with age or gender and that region was a significant factor associated with the level of PIVKA‐II. The 95% reference interval determined in this study for PIVKA‐II in Chinese healthy individuals was 28 mAU/mL, and the cutoff value which to distinguish patients with HCC from disease control groups is 36.5 mAU/mL. Conclusion: In clinical applications, it is recommended that each laboratory chooses their own reference interval based on the regional population study or cutoff value for disease diagnosis.